2021
DOI: 10.1002/dta.2945
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale evaluation of ion mobility spectrometry for the rapid detection of synthetic cannabinoid receptor agonists in infused papers in prisons

Abstract: Synthetic cannabinoid receptor agonists (SCRAs), colloquially known as “spice,” are commonly used in prisons and enter establishments via the mail in the form of infused papers. Many prisons use benchtop ion mobility spectroscopy (IMS) instruments to screen mail and seized materials for the presence of SCRAs and other controlled substances. The selectivity and sensitivity of Rapiscan Itemiser® 3E and Itemiser® 4DN Ion Trap Mobility Spectroscopy™ (ITMS™) systems were evaluated using 21 SCRA reference standards.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 28 publications
2
71
0
Order By: Relevance
“…4F‐MDMB‐BICA (methyl 2‐(([1‐(4‐fluorobutyl)‐1 H ‐indol‐3‐yl]carbonyl)amino)‐3,3‐dimethylbutanoate), the indole analogue of 4F‐MDMB‐BINACA (7) ; 5F‐EMB‐PICA (ethyl 2‐([1‐(5‐fluoropentyl)indole‐3‐carbonyl]amino)‐3‐methylbutanoate), an analogue of 5F‐MDMB‐PICA (6) ; and MMB‐4en‐PICA (17) , included in this study as an emerging compound, have been seized and reported to early warning systems in the United States 72–74 and Europe 75,76 . 5F‐EMB‐PICA and 4F‐MDMB‐BICA have been detected in Scottish prisons for the first time in May 2020 77 . Using the available CB 1 receptor structure–activity relationship (SAR) data for this class of SCRAs, we can begin to pre‐emptively evaluate/predict the relative potential for CB 1 ‐mediated harms of emerging compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4F‐MDMB‐BICA (methyl 2‐(([1‐(4‐fluorobutyl)‐1 H ‐indol‐3‐yl]carbonyl)amino)‐3,3‐dimethylbutanoate), the indole analogue of 4F‐MDMB‐BINACA (7) ; 5F‐EMB‐PICA (ethyl 2‐([1‐(5‐fluoropentyl)indole‐3‐carbonyl]amino)‐3‐methylbutanoate), an analogue of 5F‐MDMB‐PICA (6) ; and MMB‐4en‐PICA (17) , included in this study as an emerging compound, have been seized and reported to early warning systems in the United States 72–74 and Europe 75,76 . 5F‐EMB‐PICA and 4F‐MDMB‐BICA have been detected in Scottish prisons for the first time in May 2020 77 . Using the available CB 1 receptor structure–activity relationship (SAR) data for this class of SCRAs, we can begin to pre‐emptively evaluate/predict the relative potential for CB 1 ‐mediated harms of emerging compounds.…”
Section: Resultsmentioning
confidence: 99%
“…75,76 5F-EMB-PICA and 4F-MDMB-BICA have been detected in Scottish prisons for the first time in May 2020. 77 Using the available CB 1 receptor structure-activity relationship (SAR) data for this class of SCRAs, we can begin to preemptively evaluate/predict the relative potential for CB 1 -mediated harms of emerging compounds. This approach should be supported using in silico tools and utilizing the available ground-truth in vitro datasets to predict the pharmacological profiles of emerging and yet to emerge SCRA compounds.…”
Section: Pharmacological Evaluation Of Scra-infused Papers Seized In Scottish Prisonsmentioning
confidence: 99%
“…Many of the seizures received for laboratory testing were pre‐screened using IMS in situ within the prisons and found to have a positive SCRA indication. The qualitative and quantitative screening methods used have been described previously 21,22 and involve qualitative analysis by gas‐chromatography‐mass spectrometry (GC‐MS) and orthogonal confirmation by ultra‐performance liquid chromatography with photodiode array and quadrupole time of flight mass spectrometry (UPLC‐PDA‐QTOF‐MS). Selected results for samples seized between June 2018 and February 2020 have been reported previously 21–23 .…”
Section: Methodsmentioning
confidence: 99%
“…Sample information and results for samples seized up to September 2020 have been reported previously. [13][14][15]19 Sample information and analytical data for the samples not reported previously are provided in Table S1. The extraction of SCRAs from infused papers and other materials and analysis by gas chromatography-mass spectrometry (GC-MS) has been described previously.…”
Section: Introductionmentioning
confidence: 99%